2014
DOI: 10.3174/ajnr.a4046
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prognostic Value of MRI Findings in 108 Patients with Idiopathic Normal Pressure Hydrocephalus

Abstract: BACKGROUND AND PURPOSE:MR imaging is used in the diagnostic evaluation of patients with idiopathic normal pressure hydrocephalus. The aim of this study was to describe the prevalence of several imaging features and their prognostic use in the selection of shunt candidates with idiopathic normal pressure hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
168
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(187 citation statements)
references
References 27 publications
12
168
5
2
Order By: Relevance
“…Virhammar et al 21 recently investigated the neuroimaging features predictive of shunt responses in 108 patients with iNPH. These authors demonstrated that DESH and a small callosal angle, not high-convexity tightness or Sylvian fissure dilation, were associated with better shunt responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virhammar et al 21 recently investigated the neuroimaging features predictive of shunt responses in 108 patients with iNPH. These authors demonstrated that DESH and a small callosal angle, not high-convexity tightness or Sylvian fissure dilation, were associated with better shunt responses.…”
Section: Discussionmentioning
confidence: 99%
“…6) Bumps in the lateral ventricular roof, which are often observed in patients with iNPH, 21 were visually assessed on transverse sections above the top of the thalamus and rated as present (1) or absent (0). 7) Deep white matter hyperintensities (DWMHs) and periventricular hyperintensities (PVHs) were assessed according to Fazekas et al 22 Visual ratings 3-7 were independently evaluated by 2 raters (W.N.…”
Section: Mr Imaging Measuresmentioning
confidence: 99%
“…Because DESH or high-convexity tightness has been recognized as a highly sensitive radiologic finding for iNPH diagnosis, 6,19 a coronal MR imaging section has been recommended for this diagnosis. 6,20 A coronal MR imaging section is also suitable for the measurement of the z-Evans Index, the same as the DESH and callosal angle. As quantitative indices representing high-convexity tightness and the enlarged Sylvian fissure, the upper-to-lower subarachnoid space ratio and the CSF volume of the 4 segmented parts of the subarachnoid spaces were newly proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The brain morphology in iNPH is characterized by large ventricles, enlarged Sylvian fissures, tight convexity sulci, and a small callosal angle. [4][5][6] The symptoms can be relieved by removal of CSF in patients with iNPH, either permanently by shunt implantation or temporarily by a lumbar puncture as a prognostic test (CSF tap test). 7 Radiologic evaluation of the size of the ventricles and sulci is also important in patients with other types of hydrocephalus (eg, secondary to a subarachnoid hemorrhage).…”
mentioning
confidence: 99%